Teaching Law. Brief macro and micro approaches - López Guerra, Luis (EUNOMÍA. Revista en Cultura de la Legalidad, 2022)
This commentary deals with the training of legal professionals from two perspectives. On the one hand, where this training should be provided (macro perspective), and on the other and more briefly, which methodologies should be followed in each context (micro perspective). From the first perspective, the role of the university and other institutions is examined, as well as the need for a common training of a contentious-procedural nature. Viewed from a micro perspective, particular attention is given the need to adapt legal training to the growing specialization in practice areas, and to the progressive evolution of information retrieval in these matters.